Patient-Centred Counselling Tools for Dispensing Contraceptives in Community Pharmacy Settings: A Systematic Review - Vijai Indrian P; Chong WW; Ali A; Mhd Ali A (Dove Medical Press, 2024)
Parimala Vijai Indrian,1 Wei Wen Chong,1 Anizah Ali,2 Adliah Mhd Ali1 1Centre of Quality Management of Medicines, Faculty of Pharmacy, Universiti Kebangsaan Malaysia, Kuala Lumpur, Malaysia; 2Department of Obstetrics and Gynaecology, Faculty of Medicine, Universiti Kebangsaan Malaysia, Kuala Lumpur, MalaysiaCorrespondence: Adliah Mhd Ali, Faculty of Pharmacy, Universiti Kebangsaan Malaysia, Jalan Raja Muda Abdul Aziz, Kuala Lumpur, 50300, Malaysia, Tel +603-92897286, Fax +603-26983271, Email adliah@ukm.edu.myBackground: The patient-centred counselling tools are a comprehensive resource to assist community pharmacists in providing effective treatment choices and assisting with decision-making.Aim: To identify and select suitable tools community pharmacists use with targeted patient-centred outcomes for dispensing contraceptives.Methods: Five electronic databases, Web of Science, Cochrane Library, PubMed, Scopus, and Google Scholar as additional sources for published and unpublished studies, were searched to identify literature for contraceptive tools or strategies for pharmacists to decide on contraceptive choice and dispensing by pharmacist. Studies involving pharmacists or tools suitable for pharmacists from any country, published since 1990 were considered.Results: A total of 21 publications met the inclusion criteria. Robvis' tool was used for visualizing the risk of bias for each result. There were three studies that used the tools specifically by community pharmacists and others focused on general family planning users and pharmacists. The suitability of patient-centred interventions in community pharmacy settings was further evaluated.Conclusion: The evidence for special tools for pharmacists for dispensing contraceptives in community settings is limited and further research is needed to develop and evaluate novel interventions for pharmacists in community settings.Keywords: contraception, patient-centred, community pharmacist, family planning, counselling tools, dispensing contraceptives